2020
DOI: 10.3390/ijerph17145144
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Quality, Depression and Social Support Are Determinants of Serum Phosphate Level among Hemodialysis Patients in Malaysia

Abstract: Despite optimal control of serum phosphate level being imperative to avoid undesirable health outcomes, hyperphosphataemia is a highly prevalent mineral abnormality among the dialysis population. This study aimed to determine factors associated with hyperphosphatemia among hemodialysis patients in Malaysia. Multiple linear regression analysis was used to ascertain the possible factors that influence serum phosphate levels. A total of 217 hemodialysis patients were recruited. Hyperphosphatemia was prevalent. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 87 publications
1
6
1
1
Order By: Relevance
“…In previous studies, it appears that sleep quality was related to anemia 35 , 36 , hyperphosphatemia 37 , 38 , nutritional status 39 , uremic pruritus, hyperparathyroidism 40 , time on hemodialysis 35 , female 35 , 41 , age 27 , 28 , 41 , 42 ; however, in this study these associations were not verified. A study by Bilgic et al (2007) 39 found that those patients with higher malnutrition and inflammation scores had worse sleep quality, in the present study the BMI, albumin, and serum ferritin did not differ between groups.…”
Section: Discussioncontrasting
confidence: 82%
“…In previous studies, it appears that sleep quality was related to anemia 35 , 36 , hyperphosphatemia 37 , 38 , nutritional status 39 , uremic pruritus, hyperparathyroidism 40 , time on hemodialysis 35 , female 35 , 41 , age 27 , 28 , 41 , 42 ; however, in this study these associations were not verified. A study by Bilgic et al (2007) 39 found that those patients with higher malnutrition and inflammation scores had worse sleep quality, in the present study the BMI, albumin, and serum ferritin did not differ between groups.…”
Section: Discussioncontrasting
confidence: 82%
“…In this study, being unemployed appears to be the highest predicator of poor sleep. Previous research has reported similar findings [33,34]. One explanation of this result is that unemployed patients do not have a regular routine in their daily lives.…”
Section: Discussionsupporting
confidence: 61%
“…However, these strategies have been shown to be limited in promoting desirable patient behaviors to achieve optimal serum phosphorus control [ 11 ]. Issues relate to barriers such as the lack of resources and expertise for patient education [ 12 ], poor patient knowledge on phosphate management [ 13 ], and phosphate binder medication compliance [ 11 ]. It appears that HD patients have the lowest knowledge about dietary phosphorus compared to other nutrients [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%